OPTIMASI DISTRIBUSI 4-ESELON LOGISTIK OPERASI LAUT DENGAN PENDEKATAN ALGORITMA HYBRID PARTICLE SWARM OPTIMIZATION - Yohannes Enggar; Iwan Vanany; Supartono Supartono (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2016)
This study develops an optimization model 4 echelon distribution logistics sea operations that consist of multi main naval bases, multi forward naval bases, multi distributors, multi stricking force ships and multi helicopters to the method of delivery, by replenishment at sea on the rendezvous points. This model considers the selection of the modes of transportation logistics ship types are used, multi commodity share shipments at each echelons to answer the lost capacity transport modes, the cost of transportation, loading and unloading costs, defective commodity costs and the cost of losing the material generated at each frequency of deliveries to reduce the total cost of distribution. The total cost of the distribution consists of the cost in the forward naval base, logistics ship as distributor and stricking force ships. The model developed included in the category of mixed fleet transshipment and solved by the solution method based hybrid nonlinear inertia weight particle swarm optimization with multiple capacitated vehicle transshipment to generate optimal distribution costs simultaneously for all the decision variables. Conclusion derived from the results of the numerical example states that the total cost of distribution is smaller when using combination of modes of transport logistics ships larger capacity namely KRI ARN-903 and KRI ARN-903 with total efficiency of the distribution costs amounted to 46.07 % in one planning horizon.